Coronavirus disease 2019 death prediction by electrocardiographic abnormalities and elevated D-dimer levels - Chen, Jing; Wang, Yina; Wang, Jingyi; Chen, Lie; Luo, Qiushi; Wang, Bei; He, Xingwei; Li, Xuefei; Zuo, Huakun; Zuo, Ping; Yang, Xiaoyun (Frontiers in Cardiovascular Medicine, 2022)
Background: To study the electrocardiography (ECG) abnormalities and elevated D-dimer levels and evaluate their death prediction function in patients with COVID-19. Methods and Results: This retrospective cohort study enrolled 416 COVID-19 patients at Wuhan Tongji Hospital from February 1 to March 20, 2020. ECG manifestations, D-dimer levels, and in-hospital deaths were recorded for all patients. The association between ECG manifestations and hospital mortality in patients with increased D-dimer levels was performed by logistic regression analysis. In hospitalized COVID-19 patients, ST-T abnormalities (34.3%) were the most frequent ECG manifestations, whereas sinus tachycardia (ST) (13.3%) and atrial arrhythmias with rapid rhythms (8.5%) were the two most common cardiac arrhythmias. Compared to severely ill COVID-19 patients, ST-T abnormalities, ST and atrial arrhythmias with rapid rhythms, D-dimer levels, and in-hospital death were significantly more frequent in critically ill patients with COVID-19. Moreover, elevated D-dimer levels were observed in all the patients who died. The patient’s age, incidence of ST-T abnormalities, ST, atrial fibrillation (AF), and atrial premature beat of patients with elevated serum D-dimer levels were significantly higher than those in the non-elevated D-dimer subgroup. Multivariate logistic regression analysis showed that ST and AF were risk factors for hospital mortality in patients with elevated D-dimer levels. Conclusions: ECG abnormalities and increased D-dimer levels were associated with a higher risk of critical illness and death in hospitalized COVID-19 patients. ECG abnormalities, including ST and AF, combined with elevated D-dimer levels, can be used to predict death in COVID-19.